Innate and learned predator recognition across populations of Atlantic salmon, Salmo salar. (7th May 2021) - Lau, Malcolm J.; Wilson, Chris C.; Neff, Bryan D.
Abstract: Innate and learned anti‐predator responses can be important determinants of survival in natural environments. Our study measured innate and learned anti‐predator responses in three populations of Atlantic salmon, Salmo salar . Across populations, we found that the presence of a chemical alarm cue derived from the skin of conspecifics was associated with a significant decline in behavioural activity, indicating an innate anti‐predator response to the chemical alarm cue. The presence of a kingfisher model was not associated with a change in behavioural activity, indicating that this visual predator cue does not elicit an innate anti‐predator response. Following training in which the alarm cue and predator cue were paired, the presence of a kingfisher model was not associated with a change in behavioural activity, indicating the absence of a learned anti‐predator response across the three populations. Understanding population variability in anti‐predator behaviour may be important when selecting populations for reintroduction efforts of Atlantic salmon. Abstract : Our study measured innate and learned anti‐predator responses in three populations of Atlantic salmon, Salmo salar . Across populations, we observed an innate anti‐predator response to a chemical alarm cue but no response to a visual predator cue of a kingfisher model. The presence of a kingfisher model did not alter behavioural activity after training in which the alarm cue and predator cue were paired, indicating the absence of a learned anti‐predator response.